Water Quality in the dam site of the Koto Panjang dam based on Chemical Index - Utami, Dwi Ayu; Sumiarsih, Eni; ', Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
In floating cage fish culture activities, fish feed remains and feces are freed to surrounding water. Degradation of these materials decreases the water quality in general. To understand the water quality in general, a research was conducted from April to May 2015. This research aims to determine the water quality in the dam site of Koto Panjang dam, based on Chemical Index (Kirchoff, 1991). There were three stations. In each station water samples were collected from 3 different depths, in the surface; secchi depths and 2 secchi depths. Water samples were taken 3 times/ week. Water quality parameters measured were temperature, conductivity, brightness, pH, dissolved oxygen, BOD5, nitrate, phosphate and ammoniac. Results shown that water quality in the research area are as follows : Temperature 29-310C, conductivity 24.7-26.6 μS/cm, brightness 100-176 cm, pH 5-6, dissolved oxygen 4.4-6.2 mg/L, BOD5 3.2-10.2 mg/L, nitrate 0.049-0.298, phosphate 0.03-0.087 mg/L, dan ammoniac 0.03-0.182 mg/L. The value of the Chemical index was 44.19-52.97, indicates that this reservoir is fairly polluted.Keywords : Reservoir of Koto Panjang, Water Quality, Chemical Index